Business output and business experience: Evidence from China's nongovernmental businesses - SU, Liangjun (Institutional Knowledge at Singapore Management University, 2007)
We study the application of the Solow growth model in China's non-governmental businesses and propose a reasonable modification for it. Our analysis indicates that business experience is closely tied to the output of China's non-governmental businesses. Our major findings include: (1) the business experience has little overall impact on the elasticity of output with respect to labour; (2) the business experience has a large impact on the elasticity of output with respect to capital and the elasticity increases as the business experience increases; (3) the adjusted Solow residual that reflects technological progress exhibits a negative relationship with the business experience, indicating that a newly established business tends to have higher technology content than others.